Quality of Human Capital in the European Union in the Years 2004-2013. Application of Structural Equation Modelling - Adam P. Balcerzak; Michal Bernad Pietrzak (Institute of Economic Research (IER), 2016)
EU policy guidelines point out that improvement of quality of human capital (QHC) should be treated as an important factor supporting convergence process. Thus, the aim of the research is the identification of the variables that determine changes in QHC. It is assumed that QHC should be considered as a latent variable, which can be measured with application of Structural Equation Modeling (SEM). SEM includes confirmatory factor analysis and path analysis used in econometrics. In the research, the hypothetic SEM model was proposed for the years 2004-2013. Four subsets of observable variables were used: a) macroeconomic and labour market effectiveness, b) quality of education, c) national innovation system, d) health and social cohesion. The research confirmed significant influence of the proposed variables on the level of QHC and positive tendencies in changes of QHS in the EU countries.
Keywords: C30; C38; 330; Structural Equation Model (SEM); quality of human capital; European Union